Upgrading Shortest Path Problems - Shra Fatima; Kamlesh Chandra Maurya (International Journal of Engineering and Management Research, 2023)
There are several areas where the shortest path problem exists.One well-known algorithm is the Dijkstra Algorithm.The "Dijkstra Algorithm" has one flaw, according to the results of the experiments, namely that it doesn't deal with the issue of adjacent vertices in the shortest path.The algorithm has seen substantial improvement. The findings of our trial show that the problem has been successfully fixed.